1996
DOI: 10.3354/dao024035
|View full text |Cite
|
Sign up to set email alerts
|

Myxobolus nodulointestinalis sp. n. (Myxosporea, Myxobolidae), a parasite of the intestine of Barbus sharpeyi

Abstract: Large cysts about 5 mm in diameter containing mature spores were located in the muscular layer separating the intestinal serosa from the mucosa. The cysts were branched and separated by septa. They bulged deep into the lumen of the gut and the abdominal cavity. Plasmodia showed an affinity to smooth muscle cells and were covered by a degenerated layer of muscular elements. The spores, which had an elongated oval or trapezoid shape, differed in size and morphology from the known Myxobolus specles of other barbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…were pyriform in shape (Table 1), similar to those of M. miyairii, M. duodenalis (KAUR & SING, 2011) and M. cunhai (PENIDO, 1927), but distinct from the ovoid spores of M. nodulointestinalis (MASOUMIAN et al, 1996) and the spherical ones of M. bivacuolatus (NARASIMHAMURTI & KALAVATI, 1986). Spores of Myxobolus sp.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…were pyriform in shape (Table 1), similar to those of M. miyairii, M. duodenalis (KAUR & SING, 2011) and M. cunhai (PENIDO, 1927), but distinct from the ovoid spores of M. nodulointestinalis (MASOUMIAN et al, 1996) and the spherical ones of M. bivacuolatus (NARASIMHAMURTI & KALAVATI, 1986). Spores of Myxobolus sp.…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies have described infections by Myxobolus of the digestive system of freshwater fish, in particular the intestine, of cyprinids (MASOUMIAN et al, 1996;MOLNÁR, 2002;MAGAHMI et al, 2008) and catfish (Siluriformes). In siluriforms, infections have been attributed to Myxobolus bivacuolatus NARASIMHAMURTI & KALAVATI (1986), Myxobolus cunhai PENIDO (1927), and Myxobolus miyairii KUDO (1919) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…thought that M. bramae sometimes forms large plasmodia in the gill filaments of bream, while other times its spores develop in small plasmodia inside the secondary lamellae. From the combined data of the present life cycle experiments and molecular data (Molnár et al 2009) we concluded that spores developing in small plasmodia and earlier regarded as being M. bramae Masoumian et al (1996) found that a large, seemingly single cyst of Myxobolus nodulointestinalis was the amalgamation of several small plasmodia. Moreover, identified spores of M. macrocapsularis in plasmodia of M. bramae.…”
Section: Discussionmentioning
confidence: 94%
“…Myxobolus marajoensis sp. n. is smaller than the Myxobolus species found infecting cyprinid hosts, such as M. gayerae in L. cephalus (MOLNÁR et al, 2007), M. nodulointestinalis in Barbus sharpeyi Gunther, 1874(MASOUMIAN et al, 1996, and M. cyprinicola in Cyprinus carpio Linnaeus, 1758(MOLNÁR, 2002.…”
Section: Discussionmentioning
confidence: 99%